2021
DOI: 10.21203/rs.3.rs-668750/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Programmable Polymorphism of a Virus-Like Particle

Abstract: Virus-like particles (VLPs) have significant potential as both artificial vaccines and drug delivery systems. The ability to control their size has wide ranging utility, but achieving such controlled polymorphism using a single protein subunit is challenging as it requires altering VLP geometry. Here we achieve size control of MS2 bacteriophage VLPs via insertion of amino acid sequences in an external loop to shift its morphology to significantly larger forms. The resulting VLP size and geometry is controlled … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
(45 reference statements)
2
1
0
Order By: Relevance
“…These results are also consistent with recent suggestions that coupling between conformational interconversion and interaction strengths provides an important means of regulatory control over the timing and robustness of assembly [112, 134, 140, 141]. Moreover, Biela et al [142] recently demonstrated that assembly of larger capsids from MS2 capsids ( T =4 and D5) could be achieved by engineering insertions into the capsid protein that likely shift the capsid protein conformational equilibrium (analogous to changing our parameter ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are also consistent with recent suggestions that coupling between conformational interconversion and interaction strengths provides an important means of regulatory control over the timing and robustness of assembly [112, 134, 140, 141]. Moreover, Biela et al [142] recently demonstrated that assembly of larger capsids from MS2 capsids ( T =4 and D5) could be achieved by engineering insertions into the capsid protein that likely shift the capsid protein conformational equilibrium (analogous to changing our parameter ).…”
Section: Discussionsupporting
confidence: 92%
“…These results are also consistent with recent suggestions that coupling between conformational interconversion and interaction strengths provides an important means of regulatory control over the timing and robustness of assembly [112,134,140,141]. Moreover, Biela et al [142] recently demonstrated that assembly of larger capsids from MS2 capsids (T =4 and D5) could be achieved by engineering insertions into the capsid protein that likely shift the capsid protein conformational equilibrium (analogous to changing our parameter ∆g conf CD → AB ). The need for conformational specificity when accounting for HBV material properties sheds new light on previous results for a model of icosahedral capsid assembly with only one subunit species, which found that much higher values of the bending modulus, corresponding to much smaller values of the Foppl von Karman number (FvK < 0.25, compared to FvK ≈ 500 for HBV), were required to observe assembly into T =4 structures [91,143].…”
Section: Discussionsupporting
confidence: 90%
“…Similar studies have also been performed with T = 3 jelly-roll capsids (Ren et al, 2006;Barnhill et al, 2007;Lockney et al, 2011;Yildiz et al, 2012;Zeng et al, 2013;Sokullu et al, 2019;Durán-Meza et al, 2020). Understanding protein-protein interactions is an important step in improvising such systems, as was shown in a recent study on MS2 (Biela et al, 2022), where insertions were made to tweak the dimerization interface, allowing the formation of larger capsid structures.…”
Section: Capsid Asssembly and Disassembly For Understanding Infection...mentioning
confidence: 70%